CLASSROOM MANAGEMENT APPLIED BY ENGLISH TEACHER AT NINTH GRADE IN THE STATE JUNIOR HIGH SCHOOL 7 JAMBI - Faiqah Mahmudah, Faiqah mahmudah; Ummi Rahmah (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2021)
The purpose of this study was to explore the classroom management techniques utilized by the English teacher at the ninth grade level at the state junior high school 7 in Jambi. The descriptive qualitative research approach was utilized in this study, and the methods of data collection were observation, interviewing, and documentation. During the pre-activity phase, the teacher ensured that the students were prepared for the activity by ensuring that they were comfortable. The instructor also organized the seating for the students, ensured that the whiteboard and any other necessary equipment was in the appropriate location, and managed the students by providing a different manner of instruction at each meeting. During the process of learning, the instructor has the ability to foster an environment that is conducive to learning and can construct things that are constructive in order to achieve the best possible results from the learning process.